Development and validation of spectrofluorimetric method for determination of diflunisal and its impurity - Farid, Nehal Fayek; Naguib, Ibrahim Ahmed; Moatamed, Radwa Saeed; El-Ghobashy, Mohamed Refaat (European Journal of Chemistry, 2016)
A new sensitive, simple, rapid, accurate and precise spectrofluorimetric method for determination of diflunisal and its impurity is developed. Determination of diflunisal is based on first derivative spectrofluorimetric method, while its impurity can be determined by zero order spectrofluorimetric method. Diflunisal was measured at zero-crossing wavelength 394nm (zero crossing point with its impurity) which was selected for quantification of diflunisal. The impurity was measured directly at 334 nm, using 0.05 M phosphate buffer (pH = 9) as solvent. The analytical signal resulting from first derivative and zero order spectra were measured for diflunisal and its impurity, respectively. Linearity was over the range of 0.1-0.9 μg/mL for both with detection limit of 0.02 and 0.03 μg/mL and quantitation limit of 0.07 and 0.09 μg/mL for diflunisal and its impurity, respectively. The proposed method was validated as per ICH guidelines.The accuracy was checked by applying the proposed method for the determination of the drug and its impurity, the mean percentage recoveries were found to be 99.61±0.911 and 100.41±1.373 for diflunisal and its impurity, respectively. RSD values for repeatability testing were 0.268 and 0.569 and for intermediate precision were 0.224 and 0.259 for diflunisal and its impurity, respectively. The proposed method was effectively applied to analysis of studied drug in its tablet formulation. The results obtained by it were statistically compared with the reported method revealing high accuracy and good precision.